Comparative investigation effects on nervous and immune systems of bioactive water Naftussya Spa Truskavets’ and stable water solution of Boryslav’s Ozokerite - Popovych, Igor L; Gumega, Myroslav D; Verba, Igor E; Popovych, Andriǐ I; Korolyshyn, Tetyana A; Tkachuk, Svitlana P; Ostapenko, Volodymyr M; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Popovych Igor L, Gumega Myroslav D, Verba Igor E, Popovych Andriǐ I, Korolyshyn Tetyana A, Tkachuk Svitlana P, Ostapenko Volodymyr M, Zukow Walery. Comparative investigation effects on nervous and immune systems of bioactive water Naftussya Spa Truskavets’ and stable water solution of Boryslav’s Ozokerite. Journal of Education, Health and Sport. 2016;6(4):364-374. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50476 http://ojs.ukw.edu.pl/index.php/johs/article/view/3486 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2016. Revised 25.04.2016. Accepted: 25.04.2016. COMPARATIVE INVESTIGATION EFFECTS ON NERVOUS AND IMMUNE SYSTEMS OF BIOACTIVE WATER NAFTUSSYA SPA TRUSKAVETS’ AND STABLE WATER SOLUTION OF BORYSLAV’S OZOKERITE Igor L Popovych1, Myroslav D Gumega2, Igor E Verba3, Andriǐ I Popovych1, Tetyana A Korolyshyn1, Svitlana P Tkachuk2, Volodymyr M Ostapenko2, Walery Zukow4 1Laboratory of Experimental Balneology, OO Bohomolets’ Institute of Physiology NASU, Kyїv, Ukraine i.popovych@biph.kiev.ua 2Sanatorium “Kryshtalevyǐ Palats” SAD, Truskavets’, Ukraine Ostapenko.Vladimir@gmail.com 3Scientific Company “Verba”, Kyїv, Ukraine verba.igor@gmail.com 4Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl Abstract Background. It is known that biological activity of curative water Naftussya spa Truskavets’ (Ukraine) caused by its organic substances, genetically connected with Oil and Ozokerite from Boryslav’s layer, located near from Truskavets’. The low stability of water Naftusya defined our trying to reproduce its natural receiving in laboratory conditions. Aim: compare effects on nervous and immune systems of natural bioactive water Naftussya (BAWN) spa Truskavets’ and stable water solution of the Ozokerite, extracted from the Boryslav’s field. Material and research methods. The clinical approbation involved 27 volunteers with disfunction of immune and autonomous nervous system. Immune status evaluated on a set of I and II levels recommended by the WHO. About phagocytic function of neutrophils judged by activity, intensity and completeness phagocytose of Staphylococcus aureus and Escherichia coli. About state of autonomous and central nervous system judged by parameters of Heart Rate Variability (“CardioLab+HRV”) and Electroencephalogram (“NeuroCom Standard”). After testing 20 volunteers drinked BAWN while 7 others volunteers simultaneously drinked Ozokerite extract during 7 days. Daily entering of organic substances (as C organic) for both groups makes 0,3 mg/kg. Results. By method of discriminant analysis we detected 7 immune and 3 neural variables changes in which are almost identical in both groups. In particular, increases reduced levels Bacterocidity against Staph. aur., Killing Index against E. coli, Circulating Immune Complexes and Asymmetry of δ-Rhythm as well as normal levels Entropy of Immunocytogram and Immunity Integral Index while decreases raised levels Sympathetic tone, Centralization Index HRV and IgM of serum. Among variables currently not in the model it is necessary to note increasing reduced levels Bacterocidity against E. coli and Vagal tone as well as normal levels Microbial Count for Staph. aur., “active” T-Lymphocytes and Deviation α-Rhythm Frequency while decreasing raised levels Bayevskiy’s Stress Index and Activity Regulatory Systems Index HRV. Conclusion. Course drinking of stable water solution of the Ozokerite, extracted from the Boryslav’s field, imitates favourable effects of bioactive water Naftussya spa Truskavets’ on parameters of Immune and Autonomous Nervous systems at volunteers with their disfunction. Keywords: bioactive water Naftussya, Ozokerite, Immune and Autonomous Nervous systems.